Effects of Monosodium Glutamate and AminoGut on Nursery Pig Performance - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband; K. J. Touchette (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,134 nursery pigs (PIC 359 × 1050, 10.9 ± 0.46 lb BW) were used in a 42-d growth study to determine the effects of monosodium glutamate (MSG), AminoGut, and glutamine (Ajinomoto Heartland, LLC, Chicago, IL) on growth performance. Pigs were fed 1 of 6 dietary treatments. Treatments were fed in 2 phases from d 0 to 7 and 7 to 21. The dietary treatments contained 0, 0.5, 1.0, or 1.5% MSG fed in both phases, 0.8 and 0.6% AminoGut fed in phase 1 and 2, respectively, or a combination of 1.0% MSG and 0.4% glutamine fed in both phases. A common post-treatment diet was fed from d 21 to 42. Phase 1 was in pellet form and the subsequent phases were in meal form. Pigs were randomly allotted to pens at weaning and pens were then allotted to treatment according to BW in a randomized complete block design with 7 replications per treatment. During phase 1 (d 0 to 7), there was no evidence for difference (P>0.553) for ADG, ADFI, or F/G with the addition of MSG, AminoGut, or MSG+Gln. In phase 2 (d 7 to 21), the addition of MSG did not impact ADG or ADFI (P>0.163), but resulted in a marginal improvement (linear, P = 0.097) in F/G. Pigs fed AminoGut demonstrated improved ADG (P<0.05) compared to all other treatments and increased (P<0.05) ADFI compared to pigs fed 0.5, 1.0, or 1.5% MSG. There was no evidence for difference (P>0.105) during the common post-treatment period, overall period, or in final BW. Results from this study indicate that feeding MSG alone or with Gln does not result in improved post-weaning growth performance. AminoGut provided a growth and intake response from d 7 to 21 post-weaning. While the increase in BW for pigs fed AminoGut was maintained through the common phase, the response was no longer significant. Further investigation is required to determine the appropriate timing and feeding duration of AminoGut in the nursery.
Keywords: AminoGut; glutamate; glutamine; monosodium glutamate; nursery pig